First we can simplify f(x) to make it a little easier. We can write it as
4x^3+2x^2-7x+4 by combining like terms
The we just subtract g(x) from f(x) and simplify
4x^3+2x^2-7x+4-(5x^3-7x+4) and remember to distribute the negative to g(x)
4x^3+2x^2-7x+4-5x^3+7x-4 (combine like terms)
-x^3+2x^2
In factored form, this becomes
-x^2(x-2)
Hope this helps
1) 2x + 3y = 12 -> 3y = -2x +12 -> y = -2/3x + 4
2) 4y - 7x = 16 -> 4y = 7x + 16 -> y = 7/4x + 4
Answer:
Paid her: 24 because 14+6+4=24
Step-by-step explanation:
Solve your system of equations.
2x+y=1;4x+2y=−1
Solve 2x+y=1 for y:
2x+y+−2x=1+−2x(Add -2x to both sides)
y=−2x+1
Substitute (−2x+1) for y in 4x+2y=−1:
4x+2y=−1
4x+2(−2x+1)=−1
2=−1(Simplify both sides of the equation)
2+−2=−1+−2(Add -2 to both sides)
0=−3
Answer: No solution. C)
Given a quadratic equation
1. the first thing we do when we want to compete the square, is write the coefficient of x as 2 times a number.
In our case the coefficient of x is 10, so we write 10 as 2*5
2. then we write +
and -
to the expression:
Answer: